Plasmodium sporozoite phospholipid scramblase interacts with mammalian carbamoyl-phosphate synthetase 1 to infect hepatocytes - Sung-Jae Cha (Nature Portfolio, 2021)
After transmission of Plasmodium sporozoites from infected mosquitoes, parasites first infect hepatocytes. Here, Cha et al. identify a sporozoite ligand (phospholipid scramblase) and the hepatocytic receptor (carbamoyl-phosphate synthetase 1) as relevant for hepatocyte invasion and show that an antibody to hepatocyte-binding peptide 1 (HP1), which structurally mimics the sporozoite ligand, partially protects mice from infection.